PERFORMANCE ANALYSIS OF SHARIA SHARE COMPANIES USING THE PIOTROSKI F-SCORE METHOD - Didi Asmadi; Nur Izzaty; Friesca Erwan (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
Indonesia is a region that has the largest Muslim population in the world. It is a promising market opportunity to develop the Indonesian Islamic capital market. This study aims to analyze public company performance in determining the quality of sharia stocks. This study used the secondary data in historical data, namely the annual financial statements in 2017 and 2018. Meanwhile, the sample used in this study is 30 sharia stock issuers registered in the Jakarta Islamic Index. The analytical method used is the Piotroski F-Score. The study results found that there are four sharia stocks with perfect financial conditions, twenty five sharia stocks with moderate financial conditions, and one sharia stock whose financial conditions were relatively weak. This study also shows that the Piotroski F-Score method can identify Islamic stocks’ quality in the Indonesian capital market